Pruritus and long-term hemodialysis among patients with chronic renal failure - Retnaningsih, Dwi; Puspitasari, Putri; Prihati, Dyah Restuning (Intelektual Pustaka Media Utama, 2023)
Patients with hypertension and diabetes are at risk of developing chronic kidney failure. A common occurrence in patients with chronic kidney disease is pruritus. Pruritus can affect all parts of the body, which can have an emotional impact on the patient, affect the quality of sleep and mood of the patient, and cause discomfort. The study's goal was to determine whether there was a long-term link between hemodialysis and the onset of pruritus among patients with chronic renal failure who were receiving hemodialysis. Quantitative research with the cross-sectional method A total of 45 patients are in the RSI Sultan Agung Semarang Hemodialisa Unit, Central Java, Indonesia. The instrument in this study was the 5D pruritus scale. Data analysis was done using SPSS version 24. The Spearman rank test was conducted to test the relationship between two variables of the study, namely the duration of hemodialysis and the occurrence of pruritus. The study was conducted in April–June 2022, along with the ethical test. The results of the study obtained a p value of 0.004≤0.05, which means there is a relationship between long-term hemodialysis and the occurrence of pruritus in patients with chronic kidney failure. In conducting treatment, it is important to pay attention to basic needs and comfort, as well as implement pruritus management.